102 Dopamine dysregulation: not all bad news?. Issue 3 (9th February 2012) - Ali, R; Steiger, M J; Alusi, S H
Abstract : Dopaminergic therapy can result in behavioural disturbances, including impulse control disorders, punding and the dopamine dysregulation syndrome, consequences of excessive or aberrant dopamine receptor stimulation. We present two patients with the less recognised entity of hobbyism, a rare association with chronic dopaminergic therapy in Parkinson's disease and discuss its pathophysiology. Patient 1, a geography teacher, developed Idiopathic Parkinson's disease (PD) at the age of 47. Ropinirole was started in 2001 and levodopa added in 2003. He produced his first poem in 2007and has since written over 400 poems, published a Children's book on poetry and sold about 300 copies of his poetry booklet. He is currently working on a novel. Patient 2, an infant school teacher, was diagnosed in 1985 (aged 40) and treated with levodopa from disease onset. In 1993, she received a local prize for the best poem, with coverage in the local media. A book relating her PD experiences as well as containing her poetry was successfully published in 2006. Hobbyism, often arising de novo, may represent the milder end of the punding spectrum and lacks the destructive, disabling elements typically associated with punding. Its pathophysiology is ill understood but dysregulation of the dopamine receptors after prolonged dopaminergic exposure is implicated. Patients need close review for potential development of harmful impulsivity.